The Transparency Honorary Board of Election Organizers in The Violations Trial of The Election Ethics Code Organizers in Indonesia - Lulu Qurrata A'yun; Nuryanti Mustari; Ahmad Harakan; Nursaleh Hartaman (Journal of Government and Civil Society, 2022)
ABSTRACTThe spirit of the Election Organizing Honorary Council in supporting the disclosure of public information in terms of handling violations of the election organizers’ code of ethics has been seen since 2017. This study aims to determine the transparency carried out by the Election Organizers Honorary Council in Enforcement of the Code of Ethics for Election Organizers in Indonesia. The research method used is descriptive qualitative by conducting in-depth interviews with several key informants from election organizers in Indonesia with data analysis techniques using nvivo 12 plus software. The results of the study show that the Openness of the honorary election organizers council has maximized the disclosure of public information in the implementation of the trial for violations of the election organizers’ code of ethics by doing live streaming in every trial process. Furthermore, informative indicators have also been applied in implementing the transparency of election organizers by providing easy and complete access to information. Then the disclosure of the court’s decision on the enforcement of the code of ethics is carried out in real time according to the day the case decision is issued. Keywords: Transparency, election organizers, openness of public information ABSTRAKSemangat Dewan Kehormatan Penyelenggara Pemilu dalam mendukung keterbukaan informasi public dalam hal penanganan pelanggaran kode etik penyelenggara pemilu telah terlihat sejak tahun 2017. Penelitian ini bertujuan untuk mengetahui transparansi yang dilakukan oleh Dewan Kehormatan Penyelenggara Pemilu dalam Penegakan Kode etik penyelenggara pemilu di Indonesia. Metode penelitian yang digunakan adalah kualitatif deskriptif dengan melakukan wawancara secara mendalam dengan beberapa informan kunci dari penyelenggara pemilu di Indonesia dengan Teknik analisis data menggunakan software Nvivo 12 plus. Hasil penelitian menujukkan Opennes (keterbukaan) Dewan kehormatan penyelenggara pemilu telah memaksimalkan keterbukaan informasi publik dalam pelaksanaan persidangan pelanggaran kode etik penyelenggara pemilu dengan melakukan live streaming disetiap proses persidangan. Selanjutnya indicator informative juga telah diterapkan dalam pelaksanaan transparansi penyelenggara pemilu dengan menyediakan akses informasi yang mudah dan lengkap. Kemudian indicator disclosure atau pengungkapan hasil putusan persidangan penegakan kode etik dilakukan secara real time sesuai dengan hari dikeluarkannya putusan perkara. Kata Kunci: Transparansi, penyelenggara Pemilu, keterbukaan informasi publik